2017
DOI: 10.1002/rra.3163
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the recovery of fish assemblages downstream of hydrological barriers in India's Western Ghats

Abstract: River flow regulation by dams and barrages threatens freshwater fish diversity globally. However, factors contributing to the recovery of fish communities downstream of barriers to river flow are not well understood. It is crucial to identify processes that might enable river restoration despite the presence of river barriers. In this study, we assess recovery of fish species, including endemics, downstream of large and small barriers in the Malaprabha basin in the Western Ghats of India. We define "fish speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…This is especially crucial given that India's Ministry of New and Renewable Energy had, up until 2012, commissioned 1266 SHPs, and identified 6474 sites for further SHP development (MNRE, 2015). Undammed tributaries within regulated river basins must be identified for conservation, as a recent study has shown that the presence of some undammed tributaries is critical in facilitating the recovery of endemic fish species downstream of hydrological barriers in the Western Ghats (Atkore et al, ). In addition, experimental approaches to test the effectiveness of mitigation measures should be encouraged, such as the translocation of fish from dewatered regions and reservoirs to downstream regions during sediment flushing operations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially crucial given that India's Ministry of New and Renewable Energy had, up until 2012, commissioned 1266 SHPs, and identified 6474 sites for further SHP development (MNRE, 2015). Undammed tributaries within regulated river basins must be identified for conservation, as a recent study has shown that the presence of some undammed tributaries is critical in facilitating the recovery of endemic fish species downstream of hydrological barriers in the Western Ghats (Atkore et al, ). In addition, experimental approaches to test the effectiveness of mitigation measures should be encouraged, such as the translocation of fish from dewatered regions and reservoirs to downstream regions during sediment flushing operations.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of reduced stream flows, water temperatures would be higher and dissolved oxygen levels would be lower in the dammed DW location category (Anderson, Pringle, & Rojas, ). Reduced surface inflows in the dammed DW location could result in an increased relative groundwater contribution to base flows (Atkore, Kelkar, & Krishnaswamy, ). Hence, these locations would have higher pH and electrical conductivity compared with the corresponding control site. Fish community composition would vary between dammed and undammed streams.…”
Section: Introductionmentioning
confidence: 99%
“…Other local disturbances to stream biota are from intensive instream fishing and sand‐boulder mining (Atkore et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…We classified the fish based on their flow preference guild (FPG) as either rheophilic species, which are adapted to live specifically in lotic (flowing water) systems, or eurytopic species, which can live in both lotic and lentic (lakes and ponds) systems (Atkore, Kelkar, Badiger, Shanker, & Krishnaswamy, 2020; Atkore, Kelkar, & Krishnaswamy, 2017;Chakrabarty & Homechaudhuri, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In the dewatered segment, e-flow implementation may be relatively easier since this segment is immediately downstream of the reservoir. In addition, SHP design and placement of can prioritize locations such that dewatered segments can be naturally augmented by other unregulated tributaries to aid the recovery of fish assemblages (Atkore et al, 2017). However, in the downstream segment, implementing e-flows can be challenging since the pulsed discharge from the powerhouse is likely to compromise the effectiveness of e-flows.…”
Section: Management Implicationsmentioning
confidence: 99%